War and information in Colombia:or the still endless dance - Medina Pérez, Gonzalo (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
When talking about how complex the gunned conflict in Colombia is, two unavoidable questions come up. One of them asking about the viability of the hobbesian formula to figure out the sobereignty deficit existing in our country, while the other one inquires about the appropiateness of the duty for national construction, still in the development of globalization. For example, if we choose the second option, political negotiation happens to be a necessary start point, the same one which is engaged to create a political, public, colective and institutionalized order.